(untitled) (Journal of Medical & Health Sciences Review, 2025)
Purpose: This study investigates the association between spinal degenerative disease and pelvic floor dysfunction (PFD) in elderly women, aiming to determine whether spinal surgical interventions can alleviate PFD symptoms such as urinary incontinence and pelvic organ prolapse. Methods: A prospective observational study was conducted at the Neurosurgery and Spine Department of Lady Reading Hospital, Peshawar, from January 2022 to December 2024. The study included 200 women aged 50 years or older with clinical and radiological diagnoses of lumbar disc herniation, spinal stenosis, or spondylolisthesis, along with PFD symptoms. Assessment tools included the Pelvic Organ Prolapse Quantification (POP-Q) system and the International Consultation on Incontinence Questionnaire (ICIQ). Surgical interventions—lumbar decompression, spinal fusion, and laminectomy—were performed where indicated. Postoperative outcomes were followed for six months. Statistical analyses used logistic regression and paired t-tests. Results: Lumbar disc herniation was the most common spinal disorder (45%). Severe PFD was observed in 56% of those with lumbar disc herniation, 56% with spinal stenosis, and 67% with spondylolisthesis. Significant improvement in urinary incontinence was observed after lumbar decompression (65%, p < 0.01), spinal fusion (50%, p = 0.03), and laminectomy (62%, p = 0.02). Postoperative complications included persistent back pain (30%), worsened urinary symptoms (20%), and worsened pelvic organ prolapse (8%). Conclusion: There is a significant relationship between spinal degenerative disease and PFD in elderly women. Surgical treatment of spinal pathology can improve pelvic floor symptoms, but complications remain common. Multidisciplinary evaluation and rehabilitation are essential to optimize outcomes in this complex patient population.